ANXIETY AS THE TRIGGER OF SELF DEFENSE MECHANISM IN THE NOVEL SLEEPING MURDER BY AGATHA CHRISTIE - Daud, Nurul Fadila (Faculty of Letters Universitas Balikpapan, 2025)
This research is focused on the analysis of anxiety as a trigger for self-defense mechanisms in the novel Sleeping Murder by Agatha Christie. The aim is to find out the types of anxiety and to describe how anxiety triggers forms of self-defense mechanisms in the novel Sleeping Murder by Agatha Christie. To analyze the data, the researcher used a literary psychology approach by utilizing Sigmund Freud's psychoanalytic theory to examine types of anxiety and forms of self-defense mechanisms. Researchers used a descriptive qualitative research methodology, where qualitative data in the form of words were analyzed and described descriptively. Based on data analysis, this study resulted in: (1) Researchers found 3 types of anxiety that occur in a novel entitled Realistic Anxiety, Neurotic Anxiety and Moral Anxiety with a total of 28 data. Neurotic and Realistic are the most dominant types of anxiety with the same percentage of 43%; (2) Researchers showed that each type of anxiety triggers self-defense mechanisms, researchers found 6 forms of self-defense mechanisms, namely Repression, Transfer, Denial, Intellectualization, Projection, and Rationalization with a total of 22. Realistic anxiety type is the most triggering type. Triggered by a form of selfdefense mechanism displacement by (7 of 22 data).